Carbohydrate structure: the rocky road to automation. (June 2017) - Agirre, Jon; Davies, Gideon J; Wilson, Keith S; Cowtan, Kevin D
Graphical abstract: Highlights: New sugar dictionaries must have starting coordinates for a minimal-energy conformer. The current way of forcing conformation in refinement is by using torsion restraints. Torsion restraints are periodic or aperiodic. Aperiodics enforce one conformation. Recent automated building tools can deal with most common glycosylation features. Glycan interactions can now be analysed in 3D using 'Essentials' nomenclature. Abstract : With the introduction of intuitive graphical software, structural biologists who are not experts in crystallography are now able to build complete protein or nucleic acid models rapidly. In contrast, carbohydrates are in a wholly different situation: scant automation exists, with manual building attempts being sometimes toppled by incorrect dictionaries or refinement problems. Sugars are the most stereochemically complex family of biomolecules and, as pyranose rings, have clear conformational preferences. Despite this, all refinement programs may produce high-energy conformations at medium to low resolution, without any support from the electron density. This problem renders the affected structures unusable in glyco-chemical terms. Bringing structural glycobiology up to 'protein standards' will require a total overhaul of the methodology. Time is of the essence, as the community is steadily increasing the production rate of glycoproteins, and electron cryo-microscopy has just started to image them in precisely that resolution range where crystallographic methods falter most.